2003
DOI: 10.1101/gad.1029903
|View full text |Cite|
|
Sign up to set email alerts
|

Telomere-based crisis: functional differences between telomerase activation and ALT in tumor progression

Abstract: Telomerase activation is a common feature of most advanced human cancers and is postulated to restore genomic stability to a level permissive for cell viability and tumor progression. Here, we used genetically defined transformed mouse embryonic fibroblast (MEF) cultures derived from late generation mTerc −/− Ink4a/Arf −/− mice to explore more directly how telomere-based crisis relates to the evolution of cancer cell genomes and to tumor biology. An exhaustive serial analysis of cytogenetic profiles over exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(116 citation statements)
references
References 65 publications
7
108
0
1
Order By: Relevance
“…These results extend recent studies showing a prometastatic phenotype for oncogene-(including telomerase reverse transcriptase) transformed fibroblasts (29) and melanocytes (30). The fact that the telomerase inhibition reported here reduced the metastatic potential of a spontaneously arising tumor cell line, which has many genetic abnormalities other than up-regulation of telomerase, firmly establishes a role for telomerase in tumor metastasis, highlighting its importance to the lethal stages of tumor progression.…”
Section: Discussionsupporting
confidence: 75%
“…These results extend recent studies showing a prometastatic phenotype for oncogene-(including telomerase reverse transcriptase) transformed fibroblasts (29) and melanocytes (30). The fact that the telomerase inhibition reported here reduced the metastatic potential of a spontaneously arising tumor cell line, which has many genetic abnormalities other than up-regulation of telomerase, firmly establishes a role for telomerase in tumor metastasis, highlighting its importance to the lethal stages of tumor progression.…”
Section: Discussionsupporting
confidence: 75%
“…Telomerase-independent telomere maintenance that results in telomeres of normal length has been reported for primary and lymphoma cells from mouse telomerase RNA mutants (33), although other studies have revealed long and heterogeneous telomeres in mouse tumors derived in the context of telomerase deficiency (34,35). One immortalized human cell line, C3-cl6, maintained short and homogeneous telomeres in the absence of telomerase (10).…”
Section: Pot-2 Represses a Distinct Form Of Alt With Telomeres Of Normalmentioning
confidence: 99%
“…Telomere shortening in mice neither reproduces the CIN phenotype nor increases carcinogenesis if not aided by additional tumor-inducing treatment. 26,27 Instead, telomere shortening causes cell senescense, effectively blocking uncontrolled proliferation. Over the last few years, it has become clear that telomere shortening is probably a minor factor in the initiation of genomic instability, although telomerase reactivation probably plays an important role in tumor progression.…”
Section: Are Aneuploidy and Chromosome Breakage Caused By A Cingle Mementioning
confidence: 99%